Horticultural Study on Cucumber Cultivation; Pest and Disease Control from Traditional Approach - A. Nur Nasyfah Bongkang (Newinera Publisher, 2021)
The aims of the study to know Horticultural Study on Cucumber Cultivation; Pest and Disease Control from Traditional Approach. Cucumber offers several health advantages, including a high concentration of Vitamin A, anti-cancer properties, the ability to absorb pollutants, and the ability to provide energy. cucumber is high in provitamin A, which helps to preserve eye health by acting as an antioxidant. It also helps to prevent damage to body cells that leads to premature aging by acting naturally. cucumber fruit has been shown to be effective in reducing the development of intestinal cancer.